Air Bud. Golden receiver [videorecording (DVD)] - Martin, Richard, 1956-; Zegers, Kevin, 1984-; Harrison, Gregory, 1950-; Stevenson, Cynthia, 1962-; Dunn, Nora, 1952- (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2010)
When his teenage owner reluctantly becomes the school's new quarterback, Buddy catches the spirit and joins the team. The two find themselves leading the Timberwolves to the state championship. Bud's victory hopes are sidelined when two sinister Russian circus owners take a bite out of everyone's plans and dognaps Buddy for their star attraction.